2021
DOI: 10.1007/s42247-021-00173-x
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Covid-19; emerging strategies and material technologies

Abstract: It will be remembered in history as the event that brought the world together with science and technology; the COVID-19 pandemic has allowed for decades worth of progression in both healthcare policies and technology development. It has been a show of unprecedented global health policies ranging from the legal requirement for public facemask use to the use of tough movement restrictions that has bought the world’s economy to its knees. Here, we observe the impact of national lockdowns, facemask usage, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As this is the case, researchers are curious about the role of graphene and its derivatives in preventing COVID‐19 due to its antimicrobial properties. [ 183,184,207,208 ] Personal protection equipment have been one of the most important areas in dealing with COVID‐19, especially face mask use has been supported by the World Health Organization, to prevent the spread of the virus among people. With the emergence of the virus and the threat to the world, the antiviral activities of the protective face masks, have accelerated this research.…”
Section: Biocompatibility Of Graphene‐based Materialsmentioning
confidence: 99%
“…As this is the case, researchers are curious about the role of graphene and its derivatives in preventing COVID‐19 due to its antimicrobial properties. [ 183,184,207,208 ] Personal protection equipment have been one of the most important areas in dealing with COVID‐19, especially face mask use has been supported by the World Health Organization, to prevent the spread of the virus among people. With the emergence of the virus and the threat to the world, the antiviral activities of the protective face masks, have accelerated this research.…”
Section: Biocompatibility Of Graphene‐based Materialsmentioning
confidence: 99%
“…In terms of medical talent allocation, Padilla-Elías concluded that emergency talent was currently a major shortcoming of public hospitals in public health emergency response [ 16 ]. In material and equipment security analysis, Ahmed et al constructed a decision-making model for major public health emergencies based on the spatial and temporal characteristics, key events, transmission dynamics, spatial distribution, infection scale, information characteristics, and medical resource dimensions [ 17 ]. Hu et al established observation indicators that significantly promoted the clarification of prevention and control priorities, achieved early warning effects, clarified the reserve direction of emergency medical resources, and prevented the recurrence and spread of COVID-19 [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this point of view, it should be stressed that many materials used nowadays or proposed to be used in the future in highly efficient masks [61][62][63] exhibit surfaces that might be orders of magnitude larger than the geometrical area. For example, Ahmad et al [64] revealed their thoughts on the healthcare policies, developing materials and technology strategies that have contributed to reducing the damage of the pandemic, coming from the perspectives of material scientists. Alenezi et al [42] proposed a novel face mask designed as a reusable respirator with a small and highly efficient disposable fabric filter.…”
Section: The Role Of Surfacesmentioning
confidence: 99%